Chronic widespread dermatophytosis due to Trichophyton rubrum: a syndrome associated with a Trichophyton-specific functional defect of phagocytes - Sousa, Maria da Glória T. de; Santana, Grazielle B.; Criado, Paulo R.; Benard, Gil (Frontiers in Microbiology, 2015)
Dermatophytes are agents of typically benign superficial infections. However, an increasing number of severe infections in immunocompromised hosts has been reported. We aimed to understand the factors underlying the existence of a cohort of patients presenting with chronic widespread dermatophytosis (CWD) due to Trichophyton rubrum, but with no signs of immunodeficiency. Their disease is usually recurrent and difficult to manage. Fourteen patients meeting the following criteria for CWD were studied: T. rubrum culture-proven skin lesions of ≥10 cm in at least one dimension; the involvement of at least three noncontiguous localizations of >1 year’s duration; and no predisposing conditions. For comparison, we also studied 13 acute Tinea pedis patients. Macrophages and neutrophils were isolated and tested for T. rubrum conidia phagocytic and killing activity. H2O2, NO, and pro- and anti-inflammatory cytokine release were measured. All experiments were run with age- and sex-matched healthy donors’ cells in parallel. CWD patients’ macrophages and neutrophils presented with reduced T. rubrum–phagocytic and killing abilities, and reduced H2O2 and NO release when compared with those of healthy donors. CWD patients’ macrophages secreted lower levels of the proinflammatory cytokines interleukin (IL)-1, IL-6, IL-8, and tumor necrosis factor (TNF)-α, but enhanced levels of the anti-inflammatory cytokine IL-10. Neutrophil secretion closely followed this unbalanced pattern. In contrast, responses to the positive controls zymosan, lipopolysaccharide, and phorbol myristate acetate were comparable with those of healthy donors. The same experiments were performed with macrophages and neutrophils from the acute T. pedis patients and showed no differences when compared with the matched healthy donors. Patients with CWD have a T. rubrum-related functional deficiency of phagocytes and may represent a distinct clinical entity in the complex spectrum of the Trichophyton–host interaction.